2006
DOI: 10.1128/aem.72.1.848-853.2006
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization Using Peptide Nucleic Acid Probes for Rapid Detection of Mycobacterium avium subsp. avium and Mycobacterium avium subsp. paratuberculosis in Potable-Water Biofilms

Abstract: Here, we present for the first time a high-affinity peptide nucleic acid (PNA) oligonucleotide sequence for detecting Mycobacterium avium bacteria, including the opportunistically pathogenic subspecies M. avium subsp. avium, M. avium subsp. paratuberculosis, and M. avium subsp. silvaticum, by the fluorescence in situ hybridization (FISH) method. There is evidence that M. avium subsp. avium especially is able to survive and grow in drinking-water biofilms and possibly transmit via drinking water. The designed P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 33 publications
(25 reference statements)
1
46
0
1
Order By: Relevance
“…M. avium has been described to survive in biofilms for more than two to four weeks in culturable forms. Lehtola et al (2006) studied the survival of M. avium in drinking water biofilms after the spiking of the water using fluorescent in situ hybridization (FISH) with an rRNA-targeted PNA probe. They concluded that culture examination seriously underestimates the occurrence of M. avium in biofilms and water.…”
Section: The Format Usedmentioning
confidence: 99%
“…M. avium has been described to survive in biofilms for more than two to four weeks in culturable forms. Lehtola et al (2006) studied the survival of M. avium in drinking water biofilms after the spiking of the water using fluorescent in situ hybridization (FISH) with an rRNA-targeted PNA probe. They concluded that culture examination seriously underestimates the occurrence of M. avium in biofilms and water.…”
Section: The Format Usedmentioning
confidence: 99%
“…The relative hydrophobic character of PNA (peptide nucleic acid) probes compared to DNA analogues allows better diffusion through the hydrophobic cell wall of mycobacteria (19,20). However, the FISH assays available so far are restricted to differentiation of tuberculous from nontuberculous Mycobacterium species in acid-fast bacillus-positive sputum smears or in culture (2,6,15,21), as well as M. avium in potable-water biofilms (9).…”
mentioning
confidence: 99%
“…The sequence reported by Eisenach et al [43] for MTB detection by PCR was used [11,22,34,39,40,41]. This sequence was used to make both the DNA (Alpha DNA Montreal, Canada) and PNA probes (Bio-Synthesis Inc, Lewisville, TX, United States) [43,44].…”
Section: Oligonucleotide Probesmentioning
confidence: 99%
“…FISH assay was performed as described previously [34,39] (USB, Cleveland, Ohio, USA), 0.1% (vol/vol) Triton X-100 (USB, OH, USA), 50 mM Tris-HCl (Invitrogen, Carlsbad, California, USA) (pH 7.5) and a fluorescent probe with a final concentration of 1 µM. The slides were covered with cover glass and then placed in a preheated moisture chamber in the dark at 60°C for 60 minutes.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation